Terapi Herbal pada Pasien Kanker - Sagita, Rina; Widhiawati , Singgih; Setyawati , Andina (Pustaka Galeri Mandiri, 2025)
Some countries use complementary and alternative medicine (CAM) therapy in palliative care. WHO noted that 80 % of cancer patients use CAM. CAM is related to the traditional chinese medicine, acupunture, herbal preparations, vitamins, homeopathic remidies, music theraphy, psycological, physical and spiritual theraphy. A total of 600 herbal plants are used by local residents. Objective: to determine the pattern of herbal theraphy use in cancer patients. The study design used a qualitative approach. Method sampling technique with consecutive sampling of 51 patients. Results the use of herbal plants is routinely carried out by patients as much as 80,3 %. Herbal plants consumed by patients are turmeric, ginger and honey. The reason for using herbal plants are safe is 80,3 %. Patients get information about herbal plants from their families as much as 74,86 %. The use of herbal plants is routinely carried out by patients as much as 80,3 %. The use of herbal plants is the most once a day as much as 50,98 %. Conclusion: complementary herbal theraphy can be routinely recommended to the cancer patients to improve the quality of life with the recommendation of the doctor in charge of the patient